2022
DOI: 10.3390/ijerph19031286
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Coronavirus 2019 Disease Control Measures on the Incidence of Respiratory Infectious Disease and Air Pollutant Concentrations in the Yangtze River Delta Region, China

Abstract: The Yangtze River Delta is one of the top five Chinese regions affected by COVID-19, as it is adjacent to Hubei Province, where COVID-19 first emerged. We investigated the impact of COVID-19 non-pharmaceutical interventions (NPIs) on changes in respiratory infectious diseases (RIDs) incidence and air quality in the Yangtze River Delta by constructing two proportional tests and fitting ARIMA and linear regression models. Compared with the pre-COVID-19 period, the average monthly incidence of seven RIDs decrease… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
(36 reference statements)
0
5
0
Order By: Relevance
“…State Council of the People's Republic of China revised the Law of the People's Republic of China on prevention and control of infectious diseases in 2013 and 2020 4 . Moreover, several studies reported that strict precautionary measures for control of COVID‐19 epidemic including lockdowns, homestays, school closures, wearing masks, and washing hands frequently might result in changes of an epidemic of infectious disease including respiratory infectious disease, digestive tract and animal‐borne diseases, and so forth 13,14 . Therefore, it is necessary to understand the latest epidemiological characteristics of infectious diseases in China to provide a reference for summarizing the effects of past measures and formulating targeted measures in the future.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…State Council of the People's Republic of China revised the Law of the People's Republic of China on prevention and control of infectious diseases in 2013 and 2020 4 . Moreover, several studies reported that strict precautionary measures for control of COVID‐19 epidemic including lockdowns, homestays, school closures, wearing masks, and washing hands frequently might result in changes of an epidemic of infectious disease including respiratory infectious disease, digestive tract and animal‐borne diseases, and so forth 13,14 . Therefore, it is necessary to understand the latest epidemiological characteristics of infectious diseases in China to provide a reference for summarizing the effects of past measures and formulating targeted measures in the future.…”
Section: Introductionmentioning
confidence: 99%
“…4 Moreover, several studies reported that strict precautionary measures for control of COVID-19 epidemic including lockdowns, homestays, school closures, wearing masks, and washing hands frequently might result in changes of an epidemic of infectious disease including respiratory infectious disease, digestive tract and animal-borne diseases, and so forth. 13,14 Therefore, it is necessary to understand the latest epidemiological characteristics of infectious diseases in China to provide a reference for summarizing the effects of past measures and formulating targeted measures in the future. 15 Through the system, hospitals, and clinics from all 31 provinces in the Chinese mainland could report confirmed cases of infectious disease directly to the county and national Center for Disease Control and Prevention (CDC), allowing real-time information to be delivered to a central database.…”
Section: Introductionmentioning
confidence: 99%
“…The reduction in influenza cases detected during COVID-19 times might be due to many reasons, which include (i) reduced number of people with ILI/SARI visiting the health facilities as a result of mobility restrictions and lockdowns, (ii) reduced number of samples reaching the laboratory due to change in surveillance protocols, or (iii) reduced transmission of influenza virus due to implementation of non-pharmacological interventions to curb COVID-19, such as prohibition of public gatherings, closing of schools and workplaces, social distancing, use of masks, and improved hand hygiene. There is sound evidence from China, Hong Kong, USA, Singapore, and Australia that there was indeed a reduction in transmission of influenza and other respiratory diseases during the COVID-19 times [5,[14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…The SARS-CoV-2 virus had a prompt worldwide spread since it was first identified in December 2019 in Wuhan City, Hubei Province, China [ 1 , 2 , 3 ]. The new coronavirus has a genetic sequence similar to that of the first coronavirus SARSCoV, the virus that caused the 2003 severe acute respiratory syndrome (SARS) pandemic [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%